2021
DOI: 10.1038/s41467-021-24617-4
|View full text |Cite
|
Sign up to set email alerts
|

Geminiviruses encode additional small proteins with specific subcellular localizations and virulence function

Abstract: Geminiviruses are plant viruses with limited coding capacity. Geminivirus-encoded proteins are traditionally identified by applying a 10-kDa arbitrary threshold; however, it is increasingly clear that small proteins play relevant roles in biological systems, which calls for the reconsideration of this criterion. Here, we show that geminiviral genomes contain additional ORFs. Using tomato yellow leaf curl virus, we demonstrate that some of these small ORFs are expressed during the infection, and that the encode… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 89 publications
(49 citation statements)
references
References 57 publications
1
48
0
Order By: Relevance
“…But NW bipartite has AV2 genes analogue to this V2 gene of monopartite ( Sudarshana et al, 1998 ; Rojas et al, 2005 ). V3 protein is also present, essential for complete viral infection and works as an RNA silencing suppressor ( Gong et al, 2021 ). DNA-B is found in bipartite genome.…”
Section: Introductionmentioning
confidence: 99%
“…But NW bipartite has AV2 genes analogue to this V2 gene of monopartite ( Sudarshana et al, 1998 ; Rojas et al, 2005 ). V3 protein is also present, essential for complete viral infection and works as an RNA silencing suppressor ( Gong et al, 2021 ). DNA-B is found in bipartite genome.…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that we applied the 10 kDa threshold in the prediction of SbYLCV-encoded proteins, as shown in previous studies. A recent study showed that geminiviruses also encode small additional ORFs (size range 5-10 kDa) with specific subcellular localization and functions [34]. Additional ORF was also identified in the viral sense of the betasatellite genome and was demonstrated to have a critical role in virus…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, the GLDV-2 isolate encodes an ORF putatively encoding AC6 in a complementary strand sense partially overlapped with the AV1 gene, which is syntenically conserved in some OW monopartite begomoviruses belonging to the sweepovirus clade. Recently, it has been described that additional hypothetical ORFs encoded by the Tomato yellow leaf curl virus (TYLCV) genome are expressed and play a role during viral infection, implying that the repertoire of geminiviral proteins can be expanded ( Gong et al, 2021 ). A phylogenetic analysis using representative members of the main begomovirus American clades for tree construction grouped both GLDV isolates in the clade of the monopartite NW begomovirus, Tomato leaf deformation virus (ToLDeV).…”
Section: Discussionmentioning
confidence: 99%